2016
DOI: 10.1007/s00330-016-4333-3
|View full text |Cite
|
Sign up to set email alerts
|

CT dose survey in adults: what sample size for what precision?

Abstract: • Variability of dose descriptors is high regardless of the body region. • Variability of dose descriptors depends on weight selection and the region scanned. • Larger samples would reduce sampling errors of radiation dose data in surveys. • Totally or partially disabling AEC reduces dose variability and increases patient dose. • Median values of dose descriptors depend on the body weight selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Taylor et al have recently shown that samples of approximately 300 CT examinations of patients with a body weight in the range of 67–73 kg are necessary to create reliable DRLs [ 29 ]. For many years, broad application of the DRL concept has allowed national homogenisation of patient exposure in practice for specific anatomical regions [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al have recently shown that samples of approximately 300 CT examinations of patients with a body weight in the range of 67–73 kg are necessary to create reliable DRLs [ 29 ]. For many years, broad application of the DRL concept has allowed national homogenisation of patient exposure in practice for specific anatomical regions [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This small group size might not reflect the real dose exposure for the corresponding CT examination. Recently, Taylor et al reported a high variability for DLP in CT dose surveys depending on the protocol and patient weight [19]. Even when including 50 patients per protocol, a 95 % confidence interval lower than 10 % of the median (CI95 %/med< 10 %) was not reached for most protocols.…”
mentioning
confidence: 99%
“…Even when including 50 patients per protocol, a 95 % confidence interval lower than 10 % of the median (CI95 %/med< 10 %) was not reached for most protocols. Furthermore, for abdominal CT, n = 420 and for cervical spine n = 900 examinations were needed to reach the CI95 %/med< 10 % [19]. Only a few studies reported implementation of local DRLs based on systematic dose monitoring [1].…”
mentioning
confidence: 99%
“…The small sample size (n = 7 in subgroup 1 and n = 5 in subgroup 2) was an important limitation of our study, and it might have an effect on the statistical outcome. Taylor et al 32 reported a high variability of dose descriptors in their study using the data of 3805 chest CT collected by an automated exposure control system. They recommended the inclusion of greater than 190 patients to decrease the confidence interval to 10% of the median value if analyzing dose descriptors.…”
Section: Discussionmentioning
confidence: 99%